2022
DOI: 10.1128/msphere.00446-22
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacteria Mitigate the Deleterious Effects of para -Cresol in a Drosophila melanogaster Toxicity Model

Abstract: Chronic kidney disease (CKD) affects approximately 10% of the global population and has limited treatment options. The accumulation of gut microbiota-derived uremic toxins, such as para -cresol ( p -cresol) and p- cresyl sulfate, is associated with the onset of comorbidities (i.e., atherosclerosis and cognitive disorders) in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…The authors concluded that the findings correlated with a normalized intestinal microbiota [40,41]. Other explanations are feasible, such as the bifidobacteria directly sequestering p-cresol from the surrounding environment, as we have shown [27]. The data suggest that some strains of bifidobacteria are more effective than others at reducing gut microbiota-derived p-cresol, which points to the importance of proper strain selection in commercial probiotics.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…The authors concluded that the findings correlated with a normalized intestinal microbiota [40,41]. Other explanations are feasible, such as the bifidobacteria directly sequestering p-cresol from the surrounding environment, as we have shown [27]. The data suggest that some strains of bifidobacteria are more effective than others at reducing gut microbiota-derived p-cresol, which points to the importance of proper strain selection in commercial probiotics.…”
Section: Introductionsupporting
confidence: 66%
“…Each tube was spiked with 0.2 mg/mL p-cresol. The concentration of p-cresol mimicked its physiological extremes found in the human intestinal tract [27,58]. The inoculums were incubated anaerobically for 24 h at 37 • C under stationary conditions.…”
Section: P-cresol Clearance In a Simulated Colonic Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to up-regulate epithelial junction proteins or antimicrobial compounds could be added as a test for potential application [28] . A new concept suggests that some lactobacilli have the ability to dampen ATP production and impede Ca 2+ influx and contraction, which could be an assessment tool [29] , as could the ability of certain Bifidobacterium strains to internalize the renal toxin p-cresol [30] . The latter experiments were done in a Drosophila model, which is a useful tool for assessing parameters of urolithiasis [31] .…”
Section: How To Select Probiotic Strains To Reduce the Risk Of Uti An...mentioning
confidence: 99%